Fault-tolerant design and evaluation for a railway bogie active steering system. Issue 3 (4th March 2022) - Fu, Bin; Bruni, Stefano
ABSTRACT: Active suspension system can drastically improve dynamic behaviours of the railway vehicle but will also introduce safety-critical issues. The fault-tolerant analysis, therefore, is essential for the design and implementation of active suspension. However, this issue did not receive enough attention so far and only few papers can be found related to the fault tolerance of active steering for the railway vehicle. In this work, an approach based on Risk Priority Number is established to present quantitative assessment for fault tolerance of actuation system. Then this method is adopted to compare nine different active steering schemes resulting in a novel, comprehensive approach that enables a quantitative evaluation of different designs of the actuation system and of different principles to improve the fault tolerance. The impacts of typical failure modes are investigated through multi-body simulation and quantified by severity factor. Finally, the fault tolerance of different actuation schemes is evaluated by RPN values.